Endothelial Mineralocorticoid Receptor Mediates Diet-Induced Aortic Stiffness in Females. Issue 6 (18th March 2016) - Jia, Guanghong; Habibi, Javad; Aroor, Annayya R.; Martinez-Lemus, Luis A.; DeMarco, Vincent G.; Ramirez-Perez, Francisco I.; Sun, Zhe; Hayden, Melvin R.; Meininger, Gerald A.; Mueller, Katelee Barrett; Jaffe, Iris Z.; Sowers, James R.
Abstract : Rationale: : Enhanced activation of the mineralocorticoid receptors (MRs) in cardiovascular tissues increases oxidative stress, maladaptive immune responses, and inflammation with associated functional vascular abnormalities. We previously demonstrated that consumption of a Western diet (WD) for 16 weeks results in aortic stiffening, and that these abnormalities were prevented by systemic MR blockade in female mice. However, the cell-specific role of endothelial cell MR (ECMR) in these maladaptive vascular effects has not been explored. Objective: : We hypothesized that specific deletion of the ECMR would prevent WD-induced increases in endothelial sodium channel activation, reductions in bioavailable nitric oxide, increased vascular remodeling, and associated increases in vascular stiffness in females. Methods and Results: : Four-week-old female ECMR knockout and wild-type mice were fed either mouse chow or WD for 16 weeks. WD feeding resulted in aortic stiffness and endothelial dysfunction as determined in vivo by pulse wave velocity and ex vivo by atomic force microscopy, and wire and pressure myography. The WD-induced aortic stiffness was associated with enhanced endothelial sodium channel activation, attenuated endothelial nitric oxide synthase activation, increased oxidative stress, a proinflammatory immune response and fibrosis. Conversely, cell-specific ECMR deficiency prevented WD-induced aortic fibrosis and stiffness in conjunction with reductions in endothelial sodium channel activation, oxidative stress and macrophage proinflammatory polarization, restoration of endothelial nitric oxide synthase activation. Conclusions: : Increased ECMR signaling associated with consumption of a WD plays a key role in endothelial sodium channel activation, reduced nitric oxide production, oxidative stress, and inflammation that lead to aortic remodeling and stiffness in female mice. Abstract : Supplemental Digital Content is available in the text.